2004
DOI: 10.1590/s0103-20032004000200002
|View full text |Cite
|
Sign up to set email alerts
|

Economic efficiency of agricultural production in Brazil

Abstract: -This study measures levels of technical, allocative and economic efficiency in agricultural crop production for Brazil in 1995. A nonparametric frontier model (DEA) under constant returns to scale was used. On average, the results suggest that the sector suffers from moderate technical inefficiency and from strong allocative inefficiency. If full technical efficiency were achieved, the crop production would increase by more than 30% over that obtained in 1995. Land and labor were overutilized, while fertilize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
7

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 10 publications
0
7
0
7
Order By: Relevance
“…Esse baixo nível de escolaridade reflete negativamente na adoção de mudanças tecnológicas na produção, pois dificulta a assimilação de novas informações relacionadas às práticas de manejo produtivo e à qualidade do produto (Vicente, 2004;Oliveira et al, 2013).…”
Section: Resultsunclassified
“…Esse baixo nível de escolaridade reflete negativamente na adoção de mudanças tecnológicas na produção, pois dificulta a assimilação de novas informações relacionadas às práticas de manejo produtivo e à qualidade do produto (Vicente, 2004;Oliveira et al, 2013).…”
Section: Resultsunclassified
“…Fungi are usually controlled by antifungal agents during preharvest stage; however, these agents often possess adverse effects on the human health and the environment (Vicente, 2004). Repeated usage can also cause some fungi to develop resistance against broad spectrum of fungicides such as benzimidazoles, prochloraz, and imazalil.…”
Section: Fungicidesmentioning
confidence: 99%
“…Foreign scholars have done the studies on numerous aspects of agricultural production efficiency of their respect countries, including its methods, influencing factors and development directions (Goelli and Rao, 2005) [5]. Vincent (2004) adopted the data envelopment analysis (DEA) method to discuss Brazilian agricultural production efficiency, and it was shown that in Brazil, the pesticides and fertilizers had been fully utilized while other agricultural production factors failed to be fully utilized [6]. Krasachat (2000) based the study on the special national conditions of both developing countries and developed countries, analyzed the ways to improve the agricultural production efficiency respectively, and expounded the relationship between such improvements with grain production [7].…”
Section: Introductionmentioning
confidence: 99%